Pengaruh Komposisi Bahan Baku Geopolimer Terhadap Kuat Tekan - Liza Malik; Wiwik Dwi Pratiwi; Pranowo Sidi (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
Geopolymer are solid inorganic polymers produced from a chemical reaction called geopolymerization, which occurs between an alkaline solution and an aluminosilicate source. Geopolymers have been widely studied due to their known compressive strength resistance. This study aims to determine the optimal geopolymer composition for achieving compressive strength resistance. The compressive strength of geopolymers is determined by identifying the highest compressive strength value obtained from a compression test. In this study, variations in raw materials were explored, including Metakaolin at levels of 100%, 90%, 80%,70%,and 60%, Silica Fume at levels of 20%, 30%, and 40%, along with 10% Aluminium Hydroxide. The activator solutions used were Water Glass and KOH solution. The primary test conducted in this study was a compressive strength test aimed at evaluating the geopolymers strength. The results demonstrated that employing a composition of 90% Metakaolin and 10% Aluminium Hydroxide yielded the most favorable outcome. This particular composition exhibited a high compressive strength value of 40,8 MPa, with a standard deviation of ± 1,0 MPa.